Islamic compliant short term insurance: an exploratory study to develop an Islamic compliant insurance model within a South African context - Jeeva, Shakir (Rhodes University, Faculty of Commerce, Department of Accounting, 2016)
In a world where there is ever increasing risks to be mitigated, either by choice or due to the law of the country, an insurance instrument is the most popular risk mitigation tool. However, from an Islamic perspective, Muslims have certain parameters to adhere to due to the laws and boundaries as set out in the Quraan, as well as the teachings of the final prophet, Prophet Muhammed (Peace Be Upon Him). This has relevance in this context as, according to Islam, the conventional insurance models are in contravention of certain Islamic laws as they contain elements which are not acceptable in the Muslim faith. Therefore, the Islamic insurance models, or Takaful models, have removed the impermissible elements of usury, speculation, and uncertainty, which are all contained in the current conventional insurance models. By removing these impermissible elements from the insurance model, the Takaful model is acceptable for Muslims to use as a risk mitigation tool. The primary aim of the study sought to propose a short term Islamic compliant insurance model within a South African framework. The secondary aims were to ascertain the Islamic requirements for an Islamic insurance model, how these requirements fit into an insurance model, to then compare and contrast the differences between conventional insurance and Islamic insurance and, lastly, to explore awareness and attitudes towards Islamic insurance. Therefore, from the above, a proposed short term Islamic insurance model was developed within a South African context which conforms to the laws and boundaries of Islam, making this insurance model permissible to use as a Takaful tool. Additionally, semi structured interviews were conducted with certain research participants, using purposive sampling, to examine the attitudes and knowledge of the Muslim community towards the Takaful model within a South African context. It was concluded that while the majority of the research participants understand the Takaful model and the significance of this, they have chosen to use the conventional insurance offerings due to the fact that they were unaware of other Takaful alternatives, or due to the fact that the Takaful alternative was out-priced when compared to the conventional insurance offerings. It was therefore concluded that while there is a need for Takaful offerings within South Africa, this must be done in conjunction with additional marketing, education and competitive pricing for potential clients to consider this as an insurance option.
Keywords: Uncatalogued